Air Monitoring: New Advances in Sampling and Detection. (2nd January 2012) - Watson, Nicola; Davies, Stephen; Wevill, David
Abstract : As the harmful effects of low-level exposure to hazardous organic air pollutants become more evident, there is constant pressure to improve the detection limits of indoor and ambient air monitoring methods, for example, by collecting larger air volumes and by optimising the sensitivity of the analytical detector. However, at the other end of the scale, rapid industrialisation in the developing world and growing pressure to reclaim derelict industrial land for house building is driving the need for air monitoring methods that can reliably accommodate very-high-concentration samples in potentially aggressive matrices. This paper investigates the potential of a combination of two powerful gas chromatography—based analytical enhancements—sample preconcentration/thermal desorption and time-of-flight mass spectrometry—to improve quantitative and qualitative measurement of very-low-(ppt) level organic chemicals, even in the most complex air samples. It also describes new, practical monitoring options for addressing equally challenging high-concentration industrial samples.